2019
DOI: 10.3389/fcell.2019.00315
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Intercellular Wireless Communications: Exosomes in Heart Disease and Therapy

Abstract: Exosomes are nanoscale membrane-bound extracellular vesicles secreted by most eukaryotic cells in the body that facilitates intercellular communication. Exosomes carry several signaling biomolecules, including miRNA, proteins, enzymes, cell surface receptors, growth factors, cytokines and lipids that can modulate target cell biology and function. Due to these capabilities, exosomes have emerged as novel intercellular signaling mediators in both homeostasis and pathophysiological conditions. Recent studies docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 156 publications
(140 reference statements)
0
37
0
Order By: Relevance
“…Hence, miRNAs are actively transported, either by binding to RNA-binding proteins or by the inclusion in extracellular microvesicles/exosomes (named cardiosomes when derived from cardiomyocytes), allowing protection from ribonuclease-dependent degradation [20][21][22][23]. Extracellular vesicles incorporating miRNAs represent one of the most actively investigated areas in the cardiovascular field, being studied both as potential diagnostic and prognostic biomarkers in a number of cardiovascular pathologies and associated metabolic diseases [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, miRNAs are actively transported, either by binding to RNA-binding proteins or by the inclusion in extracellular microvesicles/exosomes (named cardiosomes when derived from cardiomyocytes), allowing protection from ribonuclease-dependent degradation [20][21][22][23]. Extracellular vesicles incorporating miRNAs represent one of the most actively investigated areas in the cardiovascular field, being studied both as potential diagnostic and prognostic biomarkers in a number of cardiovascular pathologies and associated metabolic diseases [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miRNAs are selectively sorted into stem/progenitor cell-derived EVs and play important roles in mediating physiological and pathological processes of cardiovascular diseases [ 15 , 31 , 32 ]. Investigation of dysregulated miRNAs in stem/ progenitor cell-derived EVs under hyperglycemic insult may provide potential therapeutic targets for rescuing EV reparative function.…”
Section: Resultsmentioning
confidence: 99%
“…55 In this context, EVs also appear to play an important role in cell-to-cell communication with important evidence now emerging to support the potential role of EVs of cardiac origin in the complex interplay between the CMs and ECs. 56 Hence, we hypothesize that the observed differences in the uptake capacity may indicate a preferential uptake of LAC-CM-EVs by hCMEC due to the enhanced cellular communication of CMs in a low glucose environment with ECs. This hypothesis is supported by recent studies showing that EVs secreted from various cardiac cells strongly interact with ECs and have the capacity to modulate their behaviour and function.…”
Section: Uptake Profile Of Lac-cm-evs By Different Human Cardiac Cellsmentioning
confidence: 94%